Duas novas espécies de Dryinidae (Hymenoptera: Chrysidoidea) de áreas de Mata Atlântica do Estado de São Paulo, Brasil - Martins, A. L.; Lara, R. I.R.; Perioto, N. W. [UNESP]; Olmi, M. (FapUNIFESP (SciELO), 2015)
Two new species of Dryinidae are described and illustrated: Dryinus auratus Martins, Lara, Perioto & Olmi sp. nov. and Gonatopus mariae Martins, Lara, Perioto & Olmi sp. nov., both from areas of Atlantic Rainforest at São Paulo State, Brazil. Keys to species are provided.
Two new species of Dryinidae (Hymenoptera: Chrysidoidea) from areas of Atlantic Rainforest at São Paulo state, Brazil
Keywords: Dryinus; Gonatopus; Malaise trap